Determining Susceptibility and Potential Mediators of Resistance for the Novel Polymyxin Derivative, SPR206, in Acinetobacter baumannii - Jacinda C. Abdul-Mutakabbir; Nana Sakyi Opoku; Karen K. Tan; Peter Jorth; Victor Nizet; Hansel M. Fletcher; Keith S. Kaye; Michael J. Rybak (MDPI AG, 2024)
With the increase in carbapenem-resistant A. baumannii (CRAB) infections, there has been a resurgence in the use of polymyxins, specifically colistin (COL). Since the reintroduction of COL-based regimens in treating CRAB infections, several COL-resistant A. baumannii isolates have been identified, with the mechanism of resistance heavily linked with the loss of the lipopolysaccharide (LPS) layer of the bacterial outer membrane through mutations in lpxACD genes or the pmrCAB operon. SPR206, a novel polymyxin derivative, has exhibited robust activity against multidrug-resistant (MDR) A. baumannii. However, there is a dearth of knowledge regarding its efficacy in comparison with other A. baumannii-active therapeutics and whether traditional polymyxin (COL) mediators of A. baumannii resistance also translate to reduced SPR206 activity. Here, we conducted susceptibility testing using broth microdilution on 30 A. baumannii isolates (17 COL-resistant and 27 CRAB), selected 14 COL-resistant isolates for genomic sequencing analysis, and performed time-kill analyses on four COL-resistant isolates. In susceptibility testing, SPR206 demonstrated a lower range of minimum inhibitory concentrations (MICs) compared with COL, with a four-fold difference observed in MIC50 values. Mutations in lpxACD and/or pmrA and pmrB genes were detected in each of the 14 COL-resistant isolates; however, SPR206 maintained MICs ≤ 2 mg/L for 9/14 (64%) of the isolates. Finally, SPR206-based combination regimens exhibited increased synergistic and bactericidal activity compared with COL-based combination regimens irrespective of the multiple resistance genes detected. The results of this study highlight the potential utility of SPR206 in the treatment of COL-resistant A. baumannii infections.